2006
DOI: 10.1152/jn.00945.2005
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory Activity of Motor Cortex in Relation to Rhythmic Whisking

Abstract: Rats characteristically generate stereotyped exploratory (5-12 Hz) whisker movements, which can also be adaptively modulated. Here we tested the hypothesis that the vibrissal representation in motor cortex (vMCx) initiates and modulates whisking by acting on a subcortical whisking central pattern generator (CPG). We recorded local field potentials (LFPs) in vMCx of behaving Sprague-Dawley rats while monitoring whisking behavior through mystacial electromyograms (EMGs). Recordings were made during free explorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 31 publications
5
26
0
Order By: Relevance
“…We have recently reported that increasing ICMS intensity significantly decreases whisking onset latency, most likely by increasing the output from 5-HT premotoneurons , consistent with the postulate that extrasynaptic transmission contributes to the delayed whisking. It is pertinent that the long latencies between cortical activation and EMG onset are consistent with our previous studies in behaving rats (Friedman et al 2006).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We have recently reported that increasing ICMS intensity significantly decreases whisking onset latency, most likely by increasing the output from 5-HT premotoneurons , consistent with the postulate that extrasynaptic transmission contributes to the delayed whisking. It is pertinent that the long latencies between cortical activation and EMG onset are consistent with our previous studies in behaving rats (Friedman et al 2006).…”
Section: Discussionsupporting
confidence: 88%
“…Inhibitory inputs are effective in rapidly terminating PICs (Heckman et al 2005), suggesting that inhibitory inputs to vMNs may be involved. Indeed, we have previously found that both the onset and offset of a whisking epoch is preceded by a brief increase in activity in vMCx (Friedman et al 2006), suggesting vMCx sends commands to both start and stop a whisking epoch.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Prolonged preparatory neural activities characteristic to human voluntary actions are also found in diverse species including monkeys (Romo and Schultz, 1987;Kato et al, 1995;Kaufman et al, 2010) and rodents (Friedman et al, 2006); this suggests that the ability to self-initiate movement is a quantifiable biological trait shared across many vertebrate species including teleost fish. The experience of agency is essential for human volitional actions (Haggard, 2008), and the pre-supplementary motor area is shown to be activated when human subjects pay attention to their intention to act (Lau et al, 2004).…”
Section: Research Articlementioning
confidence: 99%
“…As such, this procedure has enabled other difficult behavioral tasks (Gao et al, 2001;Bermejo et al, 2002;Gao et al, 2003b;Friedman et al, 2006) and intracellular (Crochet and Petersen, 2006) and extracellular (Sachdev et al, 2000;Kleinfeld et al, 2002;Melzer et al, 2006) recording studies. Yet it has been heretofore undocumented how head restraint may alter whisking behavior.…”
Section: Whisking In Head-fixed Versus Freely Exploring Animalsmentioning
confidence: 99%